Analisis Kebutuhan Bahan Ajar Pendidikan Agama Islam Berbasis Problem Based Learning dalam Penguatan Karakter Siswa - Habibullah, Muhammad Rafiq; Masykurillah; Sri Andri Astuti (PAI RAFAH, 2025)
The creation of Problem-Based Learning (PBL)-based Islamic Religious Education (PAI) teaching materials is essential to improve students' morale and critical thinking skills in facing real-world challenges. By analysing the resources used by teachers, learning barriers, and students' needs for more effective teaching materials, this study sought to analyse the need for PBL-based teaching materials. This study used descriptive quantitative methods, with data collection techniques through student questionnaires and structured teacher interviews. The results showed that 88% of 84 grade IX students at SMPN 3 Terusan Nunyai had received PAI textbooks. However, 83% of them believe that characters such as optimism, tolerance, and honesty are still lacking. In addition, 90% of students felt that the textbooks were insufficient, 95% felt that they needed more teaching resources, and 98% felt that they needed resources that could help them develop character. These results highlight the need to create PBL-based PAI modules to enhance students' educational journey and improve their critical thinking and character development. It is expected that PBL-based PAI teaching materials will be widely used in the education system to promote more contextualised and meaningful learning. Its incorporation into PAI teaching materials can be a creative way to increase the effectiveness of character learning.